Experimental study of the effect of natural fracture curvature on hydraulic fracture propagation behavior - Xun Gong; Zhijun Jin; Xinhua Ma; Yuyang Liu; Guanfang Li; Yanjun Guo (Scientific Reports)
Abstract The interaction mechanism between hydraulic fractures (HF) and natural fractures (NF) constitutes a critical research focus in hydraulic fracturing optimization. This study systematically investigates the influence of NF curvature on HF propagation behavior through large-scale true triaxial hydraulic fracturing physical simulations. The experiments were conducted on artificial rock specimens containing prefabricated fractures with varying curvature parameters. Results show that the curvature of natural fractures have important effects on the interaction between hydraulic fractures and natural fractures. When the injection rate is constant and the approximation angle is 90°, with the curvature of the natural crack gradually increasing (increasing curvature), the interaction between the hydraulic fracture and the natural fracture shows that the hydraulic fracture passes through the natural fracture and also partially extends along the natural fracture, and gradually changes to the hydraulic fracture extending only along the natural fracture, and then finally exists the natural fracture and extends along the direction of the maximum horizontal principal stress. In addition, the increase in curvature of the natural fractures leads to a decrease in fluid pressure as the hydraulic fractures interact with the natural fractures. The experimental methodology and results contribute to fundamental understanding of fracture propagation mechanics in heterogeneous media, with direct applications to stimulation design in naturally fractured reservoirs.